Cassini CIRS and ISS opposition effects of Saturn's rings – I. C ring narrow or broad surge?. Issue 2 (11th February 2019) - Déau, E; Dones, L; Spilker, L; Flandes, A; Baillié, K; Pilorz, S; Showalter, M; El Moutamid, M; Colwell, J E
Abstract: We focus on the thermal and optical opposition effects of Saturn's C ring seen by Cassini CIRS (Composite InfraRed Spectrometer) at 15.7 ${μ}$ m and ISS (Imaging Science Subsystem) at 0.6 ${μ}$ m. The opposition surge is a brightness peak observed at low phase angle (α → 0°). Saturn rings' opposition surge was recently observed in reflected light and thermal infrared emission by Cassini. There is debate on whether the C ring's thermal opposition surge width is narrow (≲1°) or broad (≳30°). This surge is important because its width was used to define the scale of ring properties driving the thermal peak. We parametrize the CIRS and ISS phase curves with several morphological models to fit the surge shape. For five of the largest C ring's plateaus, we find that their thermal surge is 10 times wider than the optical surge and that the thermal surge width (∼4°) is neither narrow, nor broad. We compare radial differences between CIRS and ISS surge morphologies with the optical depth τ (from UVIS, UltraViolet Imaging Spectrograph) and water ice band depth (from VIMS, Visual and Infrared Mapping Spectrometer) profiles. We find that: water ice band depths (microscopic ring signatures) and τ (macroscopic ring signatures) show respectively little and large contrasts between the background and the plateaus. The thermal surge amplitude and τ are correlated, and we found no band depth dependence, contrary to the optical surge amplitude, which shows no correlation with τ. These correlations suggest a macroscopic scale dominance in controlling the C ring's thermal opposition effect.